1965
DOI: 10.1146/annurev.bi.34.070165.002023
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Mechanisms in Steroid Biochemistry

Abstract: This selective review of the present status of steroid biochemistry is con fined largely to consideration of the enzymatic basis of the transformations of steroids. This subject was comprehensively reviewed in 1957 (1). The in tervening years have witnessed considerable progress toward a better under standing of the manner of formation of the truly formidable number and variety of steroids from animal, plant, and microbial sources.Although this review is oriented toward discussion of the effects of en zymes on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
34
0

Year Published

1966
1966
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(38 citation statements)
references
References 84 publications
4
34
0
Order By: Relevance
“…The microsomal fraction of liver, fortified with NADPH, has been shown to catalyze the hydroxylation of steroids, notably steroid hormones, in a number of positions of the steroid nucleus [21]. The present investigation has shown that the same subcellular fraction in the presence of NADPH catalyzes the 12a-hydroxylation of intermediates in the biosynthesis of bile acids.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…The microsomal fraction of liver, fortified with NADPH, has been shown to catalyze the hydroxylation of steroids, notably steroid hormones, in a number of positions of the steroid nucleus [21]. The present investigation has shown that the same subcellular fraction in the presence of NADPH catalyzes the 12a-hydroxylation of intermediates in the biosynthesis of bile acids.…”
Section: Discussionmentioning
confidence: 50%
“…The present investigation has shown that the same subcellular fraction in the presence of NADPH catalyzes the 12a-hydroxylation of intermediates in the biosynthesis of bile acids. When examined, the oxygen in the reaction has always been found to be derived from molecular oxygen [21]. In several cases, the mechanism of the reaction has been studied and has been found to be a direct displacement of the hydrogen in the position that is hydroxylated [21].…”
Section: Discussionmentioning
confidence: 99%
“…The achievement of this important microbial transformation has been actively pursued for several years (2,3). Some insight has recently been obtained into the mechanism of the enzymic dehydrogenation of steroids (4,5).…”
mentioning
confidence: 99%
“…However, studies during the past 10 years by several groups have provided evidence regarding sonle of the steps involved in oxygenation (1,2), isoinerization of A5-3-ltetones (2,3), and dehydrogenation (2).…”
mentioning
confidence: 99%
“…Studies on the stereocl~einical pathway for A'-dehydrogenation were carried out independently by several nrorlters (2) ; after an elegant series of experiments, Ringold et al (4) \rere able to describe the stereoche~nical pathway for the A'-dehydrogenase of Bacill~ls splzaericzls in terms of the mechanism suinn~arized in Fig. 1, in which A represents an acidic or electropl~ilic binding site a t the active center, and B a basic ainino acid side cl~ain.…”
mentioning
confidence: 99%